2022
DOI: 10.1002/jcph.2014
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Myocardial Injury in High‐Risk Patients With NSTEMI Pretreated With Ticagrelor for Less or More Than 6 Hours Before PCI

Abstract: We assessed the impact on periprocedural myocardial injury of a ticagrelor loading dose given <6 or >6 hours before percutaneous coronary intervention (PCI) in non-ST-elevation myocardial infarction (NSTEMI) patients at high risk. All consecutive patients pretreated with ticagrelor and undergoing PCI for a high-risk NSTEMI have been included in the present analysis. Propensity-score matching was performed to compare the outcomes between patients pretreated with ticagrelor for >6 hours or ≤6 hours. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The remaining number of articles was 123. Studies that did not meet the inclusion or exclusion criteria, or had unclear expressions were further eliminated by reading the full text, and 21 articles were obtained (4,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including 13 RCTs (4,5,12,14,16,(18)(19)(20)(21)(23)(24)(25)(26) and eight observational studies (11,13,15,17,22,(27)(28)(29). Literature retrieval and screening processes were carried out in accordance with the PRISMA guidelines; the specific process of screening is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining number of articles was 123. Studies that did not meet the inclusion or exclusion criteria, or had unclear expressions were further eliminated by reading the full text, and 21 articles were obtained (4,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), including 13 RCTs (4,5,12,14,16,(18)(19)(20)(21)(23)(24)(25)(26) and eight observational studies (11,13,15,17,22,(27)(28)(29). Literature retrieval and screening processes were carried out in accordance with the PRISMA guidelines; the specific process of screening is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Twenty-one studies with MACCEs were included in the analysis (119,014 patients with NSTE-ACS) (4,5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). The results of the inconsistency test showed that the inconsistency was not significant (I 2 = 4.21, P = 0.239); therefore, the consistency model was used for the analysis.…”
Section: Macces Meta-analysis Results For Maccesmentioning
confidence: 99%
See 1 more Smart Citation